The never list - Presley, Jade (Entangled Publishing, LLC, 2025)
Fifty Shades of Grey meets Serpent and the Wings of Night in a why-choose romantasy where one woman's quest to save her sister -- and the realm -- brings her to not one, but four power-hungry princes of chaos.